Perlindungan Hukum dan Pembinaan Pedagang Kaki Lima di Balikpapan - M. Soleh Pulungan (Research and Development Agency Ministry of Home Affairs, 2017)
The informal sector is very attractive because of their independence in creating jobs and providing goods/services cost. Research purposes; (1) To analyze why the street vendors (PKL) should get legal protection and guidance of the Government. (2). To analyze how policies Balikpapan City Government in the handling and coaching (PKL) in Balikpapan? Methods This study is empirical jurisdiction, in addition to reviewing the written law, also examines the legal aspects in the field of applied or implemented. Research result; In the constitutional rights of citizens to choose an occupation guaranteed by the state in accordance with Article 27 paragraph (2) of the 1945 Constitution states “Every citizen has the right to work and a decent living for humanity. Article 13 of Law Number 9 Year 1995 regarding Small Business, stated the Government shall foster a business climate in the aspect of protection, by establishing regulations and policies. in the Balikpapan City, it is needed to establish regional regulations governing the Management and Development of street vendors (PKL).